A medicinal ginger, boesenbergia rotunda: from cell suspension cultures to protoplast derived callus - Tan, Hao-Cheak; Tan, Boon-Chin; Wong, Sher-Ming; Norzulaani Khalid (Penerbit Universiti Kebangsaan Malaysia, 2016)
Boesenbergia rotunda is a medicinal ginger that has been found to contain several bioactive compounds such as boesenbergin A, panduratin A, cardamonin, pinostrobin and pinocembrin. These compounds are useful in treating various ailments, such as oral diseases, inflammation and have also been used as an aphrodisiac. In this study, an efficient protocol for developing and isolating protoplast cultures for B. rotunda has been established. Rhizome buds of B. rotunda were used as explants to initiate callus growth and the established cell suspension cultures were used to optimize their growth conditions. Our results indicated that embryogenic suspension cultures in liquid Murashige and Skoog (MS) medium supplemented with 3% (w/v) sucrose produced the highest growth rate (μ = 0.1125), whereas no promotive effect was seen in the presence of 2,4-dichlorophenoxyacetic acid and those that underwent sonication treatment. Amount of protoplasts isolated ranging from 1-5 × 105 protoplast per mL were isolated using 0.25% (w/v) macerozyme and 1% (w/v) cellulase for 24 h under continuous agitation (50 rpm) in dark condition. Of the isolated protoplasts, 54.93% were viable according to fluorescein diacetate staining test. Micro-colonies were recovered in liquid MS medium containing 9 g/L mannitol, 2 mg/L 1-naphthaleneacetic acid and 0.5 mg/L benzylaminopurine (BAP) for 4 weeks and subsequently transferred to solid MS medium supplemented with 0.5 mg/L BAP for callus initiation. The protoplast system established in this study would be useful for genetic manipulation and modern breeding program of B. rotunda.